EDTA Extractable Arsenic in Relation to Available Forms in Soil - Lee, C. K.; Low, K. S. (1990)
Ten soil smaples from cocoa estates were extracted with 10 m MEDTA solution at a soil/solution weight ratio of 1/25. Arsenic in the extract was determined by hydride generation inductively coupled plasma atomic emission spectrometry. EDTA extractable arsenic showed significant positive correlation with Al-As, Fe-As, and arsenic extracted by the methods of Mehlich I and III, Bray PI and Olsen.